Potensi Usaha Ternak Itik Pedaging dalam Meningkatkan Pendapatan Masyarakat Desa Selokgondang - Ahdiyat Agus Susilo (Fakultas Ekonomi dan Bisnis Islam, 2020)
Livestock, especially poultry, have a very good market prospect because they are supported by the characteristics of poultry products that can be accepted by the Indonesian people, with easy access and relatively low prices. This commodity is the largest contributor in national meat supply, and is a major driver of national animal protein supply. Selokgondang Village residents are entrepreneurs in the livestock sector, and the selected livestock sector is raising ducks, because besides having considerable potential as a producer of eggs and meat, but also has advantages including having a resistance to disease. Therefore, in the duck business has a relatively low risk, so it is very potential to be developed. Duck farming is a potential business opportunity. Broiler ducks are poultry producing meat that is very potential in addition to chicken. The advantage of this livestock is that it is more resistant to disease compared to purebred chickens so that its maintenance is easy and does not contain many risks. Duck meat is a source of high-quality protein and ducks are able to produce well, therefore its development is directed to fast and high production so that it is able to meet consumer demand, so the amount of income gained from raising duck meat is quite satisfying.